PRIORITAS KEBUTUHAN PELATIHAN PENYULUH PERIKANAN BERBASIS ANALISIS HIERARKI PROSES (AHP) UNTUK MENINGKATKAN KOMPETENSI ERA DIGITAL DI SATMINKAL BPPP MEDAN - Yulya Fitria; Lis M Yapanto; I Ketut Sumandiarsa (Smart Education, 2026)
Abstract: In the era of Industrial Revolution 4.0 and the transition toward Society 5.0, Indonesia's marine and fisheries sector faces a digital transformation imperative to maintain global competitiveness and resource sustainability. Fisheries extension officers, acting as agents of change, are required to possess adaptive digital competencies to facilitate technology adoption among stakeholders. However, existing training programs are often generic and lack prioritization based on real-world needs and strategic impact. This study aims to map digital competency gaps and formulate strategic training priorities by integrating individual needs with expert perspectives. The research employs a quantitative approach with a two-stage analytical design. A case study was conducted at the Base Administrative Unit (Satminkal) of the Center for Fisheries Training and Extension (BPPP) Medan. In the first stage, a Training Needs Analysis (TNA) was conducted on 230 extension officers to measure digital competency gaps across 12 indicators, followed by a Pareto Analysis to identify critical competencies (the vital few). In the second stage, the five critical competencies identified from the TNA were evaluated by a panel of nine experts using the Analytical Hierarchy Process (AHP) to determine final priorities based on four criteria: urgency, impact on performance, policy alignment, and gap severity. TNA findings revealed the highest gaps in technical competencies: